Nocturnal Road Traffic Noise Exposure and Children’s Sleep Duration and Sleep Problems - Weyde, Kjell; Krog, Norun; Oftedal, Bente; Evandt, Jorunn; Magnus, Per; Øverland, Simon; Clark, Charlotte; Stansfeld, Stephen; Aasvang, Gunn (International journal of environmental research and public health, 2017)
Almost half of the European Union (EU)’s population is exposed to road traffic noise above levels that constitute a health risk. Associations between road traffic noise and impaired sleep in adults have consistently been reported. Less is known about effects of noise on children’s sleep. The aim of this study was to examine the association between nocturnal road traffic noise exposure and children’s parental-reported sleep duration and sleep problems. The present cross-sectional study used data from The Norwegian Mother and Child Cohort Study. Parental report of children’s sleep duration and sleep problems at age 7 was linked to modelled levels of residential night-time road traffic noise. The study population included 2665 children from Oslo, Norway. No association was found between road traffic noise and sleep duration in the total study population (odds ratio (OR): 1.05, 95% confidence interval (CI): [0.94, 1.17]), but a statistically significant association was observed in girls (OR: 1.21, 95% CI: [1.04, 1.41]). For sleep problems, the associations were similar (OR: 1.36, 95% CI: [0.85, 2.16]) in girls. The ORs are presented for an increase of 10 dB. The findings suggest there is an association between road traffic noise and sleep for girls, underlining the importance of protecting children against excessive noise levels.